ANALYSIS AND DESIGN OF ACCOUNTING INFORMATION SYSTEM DATABASE OF WERKUDARA NIRWANA SAKTI CO. LTD - Karinda, Aldo Franco; Polii, Harke Revo Leonard; Pangemanan, Rifal Richard (Program Pascasarjana STIE Amkop Makassar, 2023)
Abstrak Penelitian ini bertujuan untuk mengembangkan database sistem informasi akuntansi untuk siklus transaksi pendapatan dan pengeluaran. Penelitian ini merupakan studi kasus pada Werkudara Nirwana Sakti Co. Ltd., sebuah perusahaan biro perjalanan dan event management yang masih menggunakan sistem akuntansi non-database. Penelitian ini menerapkan kerangka kerja REA (Resource-Event-Agent) dalam pemodelan basis data. Basis data dikembangkan dengan menggunakan metodologi FAST (Framework for The Application of Systems Technique). Selain FAST, kerangka kerja PIECES (Performance, Information, Economics, Control, Efficiency, Service) juga digunakan untuk menganalisis dan mengklasifikasikan masalah yang ada di Werkudara Nirwana Sakti Co. Ltd. Penelitian ini merupakan studi kasus dengan menggunakan data yang diambil dari dokumen, wawancara, dan observasi langsung. Hasil dari penelitian ini adalah sebuah rancangan basis data dalam bentuk ERD (Entity Relationship Diagram) dan diagram REA yang disesuaikan dengan kebutuhan data dan informasi akuntansi pada Werkudara Nirwana Sakti Co. Ltd. Keywords: Resource-Event-Agent (REA), Framework for The Application of Systems Technique (FAST), PIECES, Accounting Information System, Database Abstract This research is to develop an accounting information system database for a revenue and expense transaction cycle. This research is a case study on Werkudara Nirwana Sakti Co. Ltd., a travel agency and event management company which is still using a non-database accounting system. This research applies the resource-event-agent (REA) framework in database modelling. The database is developed using FAST (Framework for The Application of Systems Technique) methodology. In addition to the FAST, the PIECES (Performance, Information, Economics, Control, Efficiency, Service) Framework is also used to analyze and classify problems in Werkudara Nirwana Sakti Co. Ltd. This research is a case study using data taken from documents, interviews, and direct observations. The result of this research is a custome database design in the ERD (Entity Relationship Diagram) and the REA diagram those which are adapted to the need of data and accounting information in Werkudara Nirwana Sakti Co. Ltd. Keywords: Resource-Event-Agent (REA), Framework for The Application of Systems Technique (FAST), PIECES, Accounting Information System, Database